SCUN Delegation paid a courtesy call to UMP - Nor Asikin, Sulaiman
Universiti Malaysia Pahang (UMP) received a courtesy call by South Central University for Nationalities (SCUN), Wuhan on July 10, 2012. SCUN is UMP’s strategic alliance partner for the past three years.